Success in basketball shooting is better explained by less variability in quiet eye duration than the average quiet eye duration itself - Mizusaki, Y.; Kamei, M.; Ikudome, S.; Murata, M.; Mann, D. L.; Nakamoto, H. (Psychology of Sport and Exercise, 2025)
Gaze behavior termed quiet eye (QE), which is characterized by a fixation of long duration towards a task-relevant target at the moment of critical movement initiation, has been shown to be beneficial for performance in a variety of motor aiming tasks. Several studies, however, have questioned the effect of long QE durations for performance. Here, we show that the variability in QE duration across trials is a stronger predictor of aiming performance than the average QE duration per se. Twenty-six basketball players completed 100 free-throws with their eye movements recorded along with the free-throw accuracy. Results revealed that both the QE duration and variability were significantly correlated with free throw success rate. However, multiple regression analysis revealed that free-throw success was best explained by the QE variability (56 % explanatory rate). Mediation analysis also supported a model between QE duration and free-throw success rate mediated by QE variability. The results suggest that a longer QE duration may increase success by reducing QE variability. This provides new insights for understanding the association between QE and performance in aiming tasks.